Effect of Drought Stress on the Growth and Morphological Traits of Eucalyptus camaldulensis and Eucalyptus citriodora - Yousaf, Muhammad Sohail; Farooq, Taimoor Hassan; Ahmad, Irfan; Gilani, Matoor Mohsin; Rashid, Muhammad Haroon U; Gautam, Narayn Prasad; Islam, Waqar; Asif, Muhammad; Wu, Pengfei (PSM Biological Research, 2018)
Drought stress is the basic ecological stress in growth and development of the trees. A pot experiment was designed to analyze the growth and germination potential of Eucalyptus camaldulensis and Eucalyptus citriodora against the drought stress via completely randomized designed experiment with four replications along with four stress intervals. Seedlings were raised in pots by irrigating at four different levels i.e. 1 day (Wo), 5 day's (W1), 10 day's (W2) and 15 day's (W3). Several morphological parameters were studied. The plant height of both the species was maximum when the plants were irrigated after 1 day time interval and it gradually decreased as the irrigation interval increased. Root length varied drastically against the influence of the drought. Maximum root length 6.5 cm was observed in E. camaldulensis when the water was applied after 1 day interval followed by the E. citriodora yielding 6.1 cm of the root length against the same treatment. As the irrigation interval increased, the shoot fresh weight decreased leading to the minimum value for the shoot fresh weight at the treatment W3. Root dry weight was more as compared to E. citriodora for all treatments. Maximum root-shoot ratio (5.2) was observed in E. camaldulensis when the water was applied after 5 day interval (W1). Hence, we suggest that Eucalyptus plantation should not be done at fertile agricultural lands as its plantation can be very favorable in waterlogged and saline conditions.